Oxygen Hole Character and Lateral Homogeneity in PrNiO2+δ Thin Films - Fürsich, K.; Pons, R.; Bluschke, M.; Ortiz, R. A.; Wintz, S.; Schierle, E.; Weigand, M.; Logvenov, G.; Schütz, G.; Keimer, B.; Benckiser, E. (Frontiers in Physics, 2022)
Using x-ray absorption spectroscopy with lateral resolution from the sub-millimeter to sub-micrometer range, we investigate the homogeneity, the chemical composition, and the nickel 3d- oxygen 2p charge transfer in topotactically reduced epitaxial PrNiO$_{2+δ}$ thin films. To this end, we use x-ray absorption spectroscopy in a standard experimental setup and in a soft x-ray microscope to probe the element and spatially resolved electronic structure modifications through changes of the nickel-2p and oxygen-1s absorption spectrum upon soft-chemistry reduction. We find that the reduction process is laterally homogeneous across a partially reduced PrNiO(2+d) thin film sample for length scales down to 50 nm.